Fleksibilitas Syariat Islam dalam Modernisasi Zaman - Muhammad Ammar Raihan Prasetyo; M. Cikal Rayhan Putra Nada; M. Haris Abdillah (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
This paper discusses how Islamic law (Syariah) demonstrates flexibility in various aspects of modern life, including economics, technology, and social customs. Five specific examples of flexibility are explored to show how Syariah adapts to modern challenges. The study examines Islamic finance, medical technology, and cultural adjustments to illustrate that Syariah provides practical solutions while maintaining core principles.